HAK ATAS TANAH BAGI ORANG ASING DI INDONESIA TERKAIT DENGAN UNDANG-UNDANG NO. 5 TAHUN 1960 - Kadek Rita Listyanti; Ni Made Ari Yuliartini Griadhi (Kertha Negara : Journal Ilmu Hukum, 2014)
In Indonesia regulations on land use set forth in the Law of Agrarian Tree ( UUPA ) No . 5 The year 1960 , in which arranged UUPA prohibition on ownership of land ownership for foreigners. How does the prohibition on land ownership for foreigners ? , And the restrictions on land ownership for foreigners is no waiver of right to be used by foreigners ? . In writing the title rights over land to foreigners in Indonesia related to Law No . 5 The year 1960 , using the normative method . Ownership restrictions on foreign ownership for those set forth in Article 21 UUPA . In accordance with one of the bases in the agrarian law that is the basis of nationalism. The prohibition is intended to keep the land remains the property of the nation or citizens , because when the soil is dominated by foreign parties will diminish the well-being of their control and could cause some areas of the country by foreigners. But there are exceptions to the ban, foreigners can apply for the right to use or open a small builder.